Cross-Linguistic Variation in the Meaning of Quantifiers: Implications for Pragmatic Enrichment - Stateva, Penka; Stepanov, Arthur; Déprez, Viviane; Dupuy, Ludivine Emma; Reboul, Anne Colette (Frontiers in Psychology, 2019)
One of the most experimentally studied scales in the literature on scalar implicatures is the quantifier scale. While the truth of some is entailed by the truth of all, some is felicitous only when all is false. This opens the possibility that some would be felicitous if, e.g., 99% of the objects in the domain of quantification fall under it, a conclusion that clashes with native speakers’ intuitions. In Experiment 1 we report a questionnaire study on the perception of quantifier meanings in English, French, Slovenian and German which points to a cross-linguistic variation with respect to the perception of numerical bounds of the existential quantifier. In Experiment 2, using a picture choice task, we further examine whether the numerical bound differences correlate with differences in pragmatic interpretations of the quantifier some in English and quelques in French and interpret the results as supporting our hypothesis that some and its cross-linguistic counterparts are subjected to different processes of pragmatic enrichment.